(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
The question of the relationship between religion (faith) and science (reason) is an age old question that has hovered in the minds of intellectuals with each taking their stand as far as the matter is concerned. With the success of science, many tend to see religion as obsolete and as an opponent of science. However, Locke’s philosophy advocates for religious tolerance as a basis for civil peace and social harmony, which promotes the idea that differing beliefs can peacefully coexist. This interpretation brings forth the question of how one reconciles faith with scientific reasoning, especially when it runs contrary to traditional religious perspectives, through respect and understanding. Whitehead builds on a different aspect, proposing that both science and religion contribute to the profound intricacies of the cosmos or existence. He affirms that spiritual comprehension should take a more active role in interpreting reality through advances in science, enriching both territories rather than opposing each other. Drawing inspiration from the thoughts of these thinkers, we argue in this paper that embracing tolerance, especially self-imposed limits to hostility, can foster a more unified world where reason and faith can harmonize alongside one another.